2019
DOI: 10.1590/fst.27518
|View full text |Cite
|
Sign up to set email alerts
|

Effect of added prebiotic (Isomalto-oligosaccharide) and Coating of Beads on the Survival of Microencapsulated Lactobacillus rhamnosus GG

Abstract: The study aimed to encapsulate Lactobacillus rhamnosus GG (LGG) with the selected prebiotic, using co-extrusion technology with a poly-L-lysine (PLL) coating and evaluate probiotic survival in simulated gastrointestinal conditions. Selection of ideal prebiotic was conducted using inulin, fructo-oligosaccharide (FDS) and isomalto-oligosaccharide (OMD) and its optimal concentration to be incorporated in microencapsulation was determined. Microcapsules without coating (S 1 : no prebiotic and S 3 : with prebiotic)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 69 publications
1
11
0
1
Order By: Relevance
“…This case continued throughout the entire ripening period in our study and was clearly revealed at the end of the storage process, especially in cheese produced using probiotic cultures. The result that the microencapsulation technique used in our study significantly increases the viability levels of probiotic microorganisms has been proven by many researchers (Özer et al, 2009;Liu et al, 2017;Ningtyas et al, 2019;Siang et al, 2019).…”
Section: Discussionsupporting
confidence: 57%
“…This case continued throughout the entire ripening period in our study and was clearly revealed at the end of the storage process, especially in cheese produced using probiotic cultures. The result that the microencapsulation technique used in our study significantly increases the viability levels of probiotic microorganisms has been proven by many researchers (Özer et al, 2009;Liu et al, 2017;Ningtyas et al, 2019;Siang et al, 2019).…”
Section: Discussionsupporting
confidence: 57%
“…Prebiotics are often encapsulated with probiotics as prebiotic act as a nutrient for probiotics and give a synergistic therapeutic effect toward humans (Chan & Pui, 2020;Siang et al, 2019;Yong et al, 2020).…”
Section: According To World Health Organization and Food And Agriculturementioning
confidence: 99%
“…Moreover, the co‐extrusion technique is conducted in a sterile environment with mild conditions, hence it is suitable to be used for sensitive bioactive materials such as probiotics (Shinde et al., 2014; Silva et al., 2016). Prebiotics are often encapsulated with probiotics as prebiotic act as a nutrient for probiotics and give a synergistic therapeutic effect toward humans (Chan & Pui, 2020; Siang et al., 2019; Yong et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, probiotics are recognized as natural food preservatives and important factors for preventing diseases, controlling bacterial and fungal contamination, and improving human and animal health. In general, probiotic bacteria affect other microorganisms through changing the pH and glucose levels of the intestinal environment, secreting enzymes and antimicrobial toxins, changing the expression of pathogenic genes and competition on food intake (Kerry et al, 2018;Zhang et al, 2018;Akarca, 2020;Siang et al, 2019;Mituniewicz-Małek et al, 2019;Lucatto et al, 2020).…”
Section: Introductionmentioning
confidence: 99%